Dysfunctional HCN ion channels in neurological diseases - DiFrancesco, Jacopo C.; DiFrancesco, Dario (Frontiers in Cellular Neuroscience, 2015)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are expressed as four different isoforms (HCN1-4) in the heart and in the central and peripheral nervous systems. HCN channels are activated by membrane hyperpolarization at voltages close to resting membrane potentials and carry the hyperpolarization-activated current, dubbed If (funny current) in heart and Ih in neurons. HCN channels contribute in several ways to neuronal activity and are responsible for many important cellular functions, including cellular excitability, generation and modulation of rhythmic activity, dendritic integration, transmission of synaptic potentials and plasticity phenomena. Because of their role, defective HCN channels are natural candidates in the search for potential causes of neurological disorders in humans. Several data, including growing evidence that some forms of epilepsy are associated with HCN mutations, support the notion of an involvement of dysfunctional HCN channels in different experimental models of the disease. Additionally, some anti-epileptic drugs are known to modify the activity of the Ih current. HCN channels are widely expressed in the peripheral nervous system and recent evidence has highlighted the importance of the HCN2 isoform in the transmission of pain. HCN channels are also present in the midbrain system, where they finely regulate the activity of dopaminergic neurons, and a potential role of these channels in the pathogenesis of Parkinson’s disease has recently emerged. The function of HCN channels is regulated by specific accessory proteins, which control the correct expression and modulation of the neuronal Ih current. Alteration of these proteins can severely interfere with the physiological channel function, potentially predisposing to pathological conditions. In this review we address the present knowledge of the association between HCN dysfunctions and neurological diseases, including clinical, genetic and physiopathological aspects.